Serologic study of the A/New Jersey/8/76 influenza virus in Brazilian population groups: communication - Candeias, J. A. N.; Rácz, M. L.; Oliveira, S. O. (Revista de Saúde Pública, 1976)
Serum samples from different groups of the Brazilian population were examined for their haemagglutination inhibiting antibody content to the A/New Jersey/8/76 influenza virus with the following results: 7.8% of normal children and 75.0% of normal adults had titres of 80 or higher; in a group of Brazilian indians all the serum samples had titres of 40 or lower.